Uses of Free Time by Young Adults in Arab Mediterranean Countries: Exposing and Addressing Boundary Issues in Leisure Studies - Roberts, Ken; Kovacheva, Siyka; Kabaivanov, Stanimir (International Journal of Humanities and Social Science Research, 2018)
Evidence on uses of free time in non-Western societies exposes and forces us to address several boundary problems in leisure studies. A combination of qualitative and quantitative evidence from nationally representative samples of 15-29 year olds in Algeria, Egypt, Lebanon, Morocco and Tunisia finds some familiar divisions in the age group’s use of free time – by social class and gender. However, the evidence also reveals some region-specific features: namely that for many young people free time is less clearly separated from the rest of life than in Western societies, work and play are frequently fused, and religious and political participation are sometimes pivotal in young people’s bundles of free time activities (youth sub-cultures).